The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s13592-016-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Nest architecture, life cycle, and natural enemies of the neotropical leafcutting bee Megachile (Moureapis) maculata (Hymenoptera: Megachilidae) in a montane forest

Abstract: -Studies on the nesting biology of cavity nesting hymenoptera (bees and wasps) have stimulated many questions related to the behavior, life cycle, trophic niche, and sex ratio to better understanding of the life history of insects. Leafcutting bees are common insects, and many are important and efficient pollinators of crops and other plants. We studied the nesting biology of Megachile (Moureapis ) maculata in a montane semi-deciduous forest in Brazil using trap nests in order to improve the knowledge of aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The bees cut and collect circular to elliptical leaf pieces (Figure ) and line the brood cells with a roll of layered discs. A single brood cell may contain 50–100 leaf discs; depending on the size of the cavity, an aboveground nest may contain 1–11 brood cells (MacIvor, ; Sabino & Antonini, ), while the subterranean nests contain a single brood cell (Williams et al., ). The leaf discs are also used to partition the brood cells.…”
Section: Introductionmentioning
confidence: 99%
“…The bees cut and collect circular to elliptical leaf pieces (Figure ) and line the brood cells with a roll of layered discs. A single brood cell may contain 50–100 leaf discs; depending on the size of the cavity, an aboveground nest may contain 1–11 brood cells (MacIvor, ; Sabino & Antonini, ), while the subterranean nests contain a single brood cell (Williams et al., ). The leaf discs are also used to partition the brood cells.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high richness and wide distribution, only a few studies have reported the nesting biology of species from this subgenus (Ihering, 1904;Laroca, 1991;Teixeira et al, 2011;Cardoso & Silveira, 2012;Sabino & Antonini, 2017). Here we provide notes on a nest of Megachile (Moureapis) apicipennis Schrottky (Megachilidae) built in an abandoned nest of Xylocopa frontalis (Olivier) (Apidae).…”
mentioning
confidence: 98%
“…(Laroca, 1991;Teixeira et al, 2011;Cardoso & Silveira, 2012;Sabino & Antonini, 2017) except for Ihering (1904). According to this author, the brood cell walls of a M. apicipennis nest were constructed with mud rather than with pieces of leaves.…”
mentioning
confidence: 99%
See 2 more Smart Citations